Selected Lectures of the Meeting "From the First Thousand Days to Aging: Life is a Continuum. Epigenetics, Artificial Intelligence and Environmental Impact"; Cagliari (Italy); October 25, 2024 - - (Hygeia Press di Corridori Marinella, 2024)
Selected Lectures of the Meeting "From the First Thousand Days to Aging: Life is a Continuum. Epigenetics, Artificial Intelligence and Environmental Impact"; Cagliari (Italy); October 25th, 2024   The Meeting "From the First Thousand Days to Aging: Life is a Continuum. Epigenetics, Artificial Intelligence and Environmental Impact" is a Satellite Meeting of the 20th International Workshop on Neonatology and Pediatrics, Cagliari (Italy), October 23rd-26th, 2024.   LECT 1. THE POWER OF EPIGENETICS IN THE FIRST THOUSAND DAYS • V. Fanos (Cagliari, Italy) LECT 2. EPIGENETICS DETERMINING CHILD DEVELOPMENT AND ADULT HEALTH • M. Stanton (Lübeck, Germany) LECT 3. EPIGENETIC FACTORS INFLUENCING LONGEVITY: A PRELIMINARY STUDY • B. Pische, A.M. Posadino, P. Maccioccu, V. Tanca, G. Terziani, G. Fenu Pintori (Sassari and Brescia, Italy) LECT 4. MITOCHONDRIAL EPIGENETIC APPROACH IN NEURODEVELOPMENTAL IMPAIRMENTS • M. Greco, G. Terziani, G. Damaschi (Rivalta di Torino and Brescia, Italy) LECT 5. MANAGING LIFE BEFORE, DURING AND AFTER PREGNANCY • S. Nava (Milan, Italy) LECT 6. INTEGRATED CLINICAL APPROACH • B. Allegrini (Monopoli, Italy) LECT 7. EPIGENETIC MODULATION OF INFLAMMATION • K. Wulhfard (Turin, Italy) LECT 8. NUTRACEUTICALS AND PHYSIOLOGICAL OXYGEN MODULATION • S. Benedetti, F. Palma, B. Nuvoli, R. Galati, G. Fenu Pintori, M. Greco, G. Terziani (Urbino, Rome, Sassari, Rivalta di Torino and Brescia, Italy)